A manifestação da emoção na tradução audiovisual: dublagem em português de filmes em inglês - Lapastina, Lívia (2019)
In the act of dubbing, synchronize the script translation to the vocal and facial expressions of the actor in certain situations of challenge of adequacy of vocabulary, contextualization and selection of segmented and prosodic segments for an expression of meanings. Among the elements used by the speaker that influence the perception of the senses, we highlight the emotions. This study had aimed to confront the emotions perception in statements interpreted by the actor of the film submitted to dubbing and by the voice actor, focusing, through a semantic differential test, as it happens since the vocal quality analysis of the original actor of the English-language film and the voice of the Brazilian dubbing actor. The labels selected to compose the semantic differential test was based on the seven-basic emotions, a work by Scherer (2005). The stumulus were taken from the films entitled Alice in Wonderland and Alice Through the Looking Glass, and theirs adaptations for Brazilian cinema, focus on character Mad Hatter voice. The evaluation of the tets was performed by a group of judges, bilingual speakers, between 14 and 18 years old. The results pointed out that the voice of the actor in the original film aroused effects of similar emotions in relation to its dubbing. Both actors used voice quality settings that provoked similar meaning effects, allowing the vocal characterization of this character to lead to the expected emotional and psychological construction